Systematic literature review: Effectiveness of augmented reality in mathematics learning for students in Indonesia - Mubarok, Wildan Khusni; Anugrah, Sherlynggar (Universitas Sultan Ageng Tirtayasa, 2024)
The concept of learning media can be understood as a tool used as an intermediary between instructors and students during the learning process. The primary purpose of this tool is to provide information and channel messages, thus enabling effective and efficient learning. The aim of this study is to conduct a comprehensive literature review on the use of Augmented Reality (AR) as a form of learning media in the context of mathematics education. The research methodology employed in this study is the Systematic Literature Review (SLR) approach, which aims to identify, examine, evaluate, and interpret relevant articles. The data collection process involved documenting all articles that were similar in nature to the current research report. The study utilized a total of 20 articles, sourced from both national and international journals, which were retrieved from the Google Scholar database. The findings of the research indicate that the use of Augmented Reality as a learning medium can be beneficial and well-suited for learning mathematics, as it has the potential to improve learning outcomes and enhance students' mathematical capabilities.